Current situation of mental fatigue and its correlation with social support for elite athletes - Zhou, Y.; Guo, Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction The previous studies on sports mental fatigue focus on the analysis and description of its concept, causes and monitoring. Earlier studies have also explored the theoretical model for mental burnout. This study focused on the practical use. This paper aims to understand the present situation of mental fatigue and its correlation with social support. Further the paper will also investigate individual differences of mental fatigue and discuss the effects of demographic variables and social support for sprts related mental fatigue. The findings will provide a reference for the team to prevent, reduce or handle mental fatigue problems of athletes. Methods Participants were 100 elite athletes. The process include the measurements using three scales: Mental Fatigue Scale, Social Support Review Scale, and Perceived Social Support Scale which are conducted by professional researchers and SPSS 10.0 is used for reliability test, single sample T-test, one-way ANOVA, Pearson correlation analysis and stepwise regression. The coefficients for the three scales are high and questionnaires have good reliability. Results Findings indicate that 22% of elite athletes had frequent feelings of extreme fatigue, 16% of them had the negative emotions towards training. Approximately 47% of reported never experiencing the pleasure of success. There was a significant difference for sport mental fatigue between the genders and athletes of different levels. There was a negative correlation between social support factors and sport fatigue factors. Also the findings revealed a significant negative correlation between social support factors and sense of achievement except subjective support and the total of social support. This trend also exists between objective support and negative evaluation factor. Objective support is a part of the stepwise regression equation for mental fatigue total. Conclusions Mental fatigue symptoms of elite athletes are fairly distinctive which are mainly shown by emotional/physical burnout and negative sport evaluation. The pleasure of success may be the main reason for personal sense of achievement. There are individual differences related to mental fatigue for elite athletes and more attention should be paid to male athletes about the emotional/physical burnout, negative evaluation, and elite athletes` decreased of sense of achievement. Adjustments could be made to the training plan and load according to the individual differences to lessen fatigue. For mental fatigue, social support is one of its influential factors which mainly results in effects on the decreased of sense of achievement factor. Social support is one important resource for athletes to keep their sense of achievement. Furthermore, it shows that the main factors for mental fatigue are intensive training and emotional/physical burnout for competition.